2005
DOI: 10.1038/sj.emboj.7600604
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal role of AtSUVH2 in heterochromatic histone methylation and gene silencing in Arabidopsis

Abstract: SU(VAR)3-9 like histone methyltransferases control heterochromatic domains in eukaryotes. In Arabidopsis, 10 SUVH genes encode SU(VAR)3-9 homologues where SUVH1, SUVH2 and SUVH4 (KRYPTONITE) represent distinct subgroups of SUVH genes. Loss of SUVH1 and SUVH4 causes weak reduction of heterochromatic histone H3K9 dimethylation, whereas in SUVH2 null plants monoand dimethyl H3K9, mono-and dimethyl H3K27, and monomethyl H4K20, the histone methylation marks of Arabidopsis heterochromatin are significantly reduced. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
241
3
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(259 citation statements)
references
References 49 publications
11
241
3
2
Order By: Relevance
“…In Arabidopsis, SUVH4 (KYP), the best studied member of this class, represses expression of the floral homeotic gene, SUPERMAN (SUP), through its H3K9 methyltransferase activity [90]. Naumann et al [91] reported that the N-terminus and YDG domain in SUVH2 are involved in directing DNA methylation and subsequent histone methylation at its target locus so that heterochromatic methylation marks are affected in suvh2 mutant plants. Recently, Ebbs et al [92,93] showed that there is a hierarchical and locusspecific control of H3K9 di-methylation as well as non-CG DNA methylation by SUVH4, SUVH5 and SUVH6 HMT in Arabidopsis.…”
Section: Class V: Suppressor Of Variegation [Su(var)] Homologs and Rementioning
confidence: 99%
“…In Arabidopsis, SUVH4 (KYP), the best studied member of this class, represses expression of the floral homeotic gene, SUPERMAN (SUP), through its H3K9 methyltransferase activity [90]. Naumann et al [91] reported that the N-terminus and YDG domain in SUVH2 are involved in directing DNA methylation and subsequent histone methylation at its target locus so that heterochromatic methylation marks are affected in suvh2 mutant plants. Recently, Ebbs et al [92,93] showed that there is a hierarchical and locusspecific control of H3K9 di-methylation as well as non-CG DNA methylation by SUVH4, SUVH5 and SUVH6 HMT in Arabidopsis.…”
Section: Class V: Suppressor Of Variegation [Su(var)] Homologs and Rementioning
confidence: 99%
“…It is also associated with pericentromeric regions and with DNA methylation (Bernatavichute et al, 2008), another modification that contributes to chromatin remodeling. SUVH2 is important for the mono-and dimethylation of H3K9, but suvh2 mutant plants also show alterations in monoand dimethyl H3K27 and monomethyl H4K20 levels (Naumann et al, 2005).…”
Section: Histone Methylasesmentioning
confidence: 99%
“…The suvh and suvr alleles (in Columbia) contain mutations in genes related to KYP that contain SET domains predicted to methylate histone 3 (20). The mutants include a T-DNA insertion in SUVH2, a gene recently described as being essential for an array of repressive histone methylation marks (19). These mutants were examined by a combination of Northern blots and RT-PCR of nonvernalized and vernalized tissue ( Fig.…”
Section: Single Suvh and Suvr Mutants Are Still Responsive To Vernalimentioning
confidence: 99%
“…A major contributor to H3K9me2 in Arabidopsis is KRYPTONITE (KYP), a member of the Su-(var)3-9 class of histone methyltransferases first isolated from Drosophila (16) and identified in Arabidopsis through its role in transcriptional silencing of both endogenous genes and transgenes (17,18). Recently, a related protein SUVH2 was shown to have in vitro histone methyltransferase activity and to be required in vivo for H3K9, H3K27, and H4K20 methylation (19). KYP and SUVH2 are 2 of 14 members constituting the Arabidopsis SUVH͞SUVR class of proteins that contain SET domains predicted to methylate histone 3 (20).…”
mentioning
confidence: 99%